A bibliometric and content analysis of UP School of Library and Information Studies theses on health sciences librarianship - Celajes, Kia C.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Since trends in health sciences librarianship are mostly drawn from the Western countries like the United States, it is important to know the existing developments in health sciences librarianship in a local context. This study examined the content and bibliometric characteristics of the UP School of Library and Information Studies theses relating to health sciences librarianship from academic year 1996-1997 to 2015-2016. Specifically, the study identified the subjects, different research methods and analytical techniques used in analyzing health sciences librarianship studies, the most cited type of reference material, the most cited author, the most cited book, and the most cited journal publication.
Bibliometric and content analysis was conducted on 71 theses and generated a total of 2,756 citations. The study found out that most of the theses in health sciences librarianship are focused on applied areas (88.73%), specifically studies regarding materials and collections (69.44%). Most of the studies utilized domain analysis (53.52%) and survey research (35.21%) when conducting their theses. The most popular analytical techniques were qualitative (53.52%) and quantitative descriptive (29.57%) methods. Results from bibliometric analysis revealed that theses and dissertations (28.85%) are the most cited reference type by the researchers.
The concentration of applied topics in health sciences librarianship only emphasizes that there is a need to expand the topics on health sciences librarianship. Theoretical topics and related topics should be more studied. Analytical techniques can be more sophisticated in terms of integrating more complex inferential statistics. The usage of theses and dissertations by health sciences librarianship researchers suggests that they are regarding their own peers'works as reliable source of information. The combination of content and bibliometric analysis is not only useful for collection development of libraries, but it also identifies certain orientations of researchers in terms of the subjects they are interested in studying, how they do their theses, their techniques in doing so, and their selection of reliable materials.
Thesis (Bachelor of Library and Information Science)
Keywords: Bibliometrics; Bibliometrics -- Analysis; Content analysis (communication); Medical librarianship